Acute kidney injury with oxalate deposition in a patient with a high anion gap metabolic acidosis and a normal osmolal gap - Tarek Alhamad; Jimena Blandon; Ana T. Meza; Jorge E. Bilbao; German T. Hernandez (Society of Diabetic Nephropathy Prevention, 2013)
Background: Ethylene glycol ingestion can lead to acute kidney injury from tubular deposition of oxalate crystals. The diagnosis of ethylene glycol intoxication is based on a history of ingestion, clinical examination, high anion gap metabolic acidosis, high osmolal gap, and a measured serum level of ethylene glycol. However, depending on the delay in time from ingestion to arrival to a hospital, the osmolal gap may become normal, thereby creating a confusing clinic picture for the treating clinician. Case: A 71 year-old man with a history of alcohol abuse had been unconscious for an unknown period of time. Upon hospitalization, he was found to have a high anion gap metabolic acidosis but a normal serum osmolal gap and subsequently developed acute kidney injury. The serum lactic acid and glucose levels were unremarkable, and there were no ketones in the serum. Urine analysis showed numerous red blood cells and calcium oxalate crystals. The renal biopsy showed multiple oxalate crystals in the renal tubules demonstrating birefringence under polarized light. Given the history of alcohol abuse, the clinical presentation, the unexplained high anion gap metabolic acidosis, and the biopsy findings, ethylene glycol intoxication was deemed the most likely diagnosis. Conclusions: In cases of ethylene glycol intoxication, a high serum osmolal gap is supportive of ethylene glycol intoxication, but a normal serum osmolal gap does not exclude the diagnosis, especially when the time of ingestion is unknown. Physicians should be aware of potentially normal serum osmolal gap values in cases of ethylene glycol intoxication.